Lessons From Hollywood a New Approach To Funding R & D - Lo, Andrew; Pisano, Gary (MIT Sloan Management Review, 2016)
Science-based industries such as biotechnology offer the potential of high growth, but they are fraught with risk. The payoffs can take many years to materialize or may never come. Even though the traditional venture capital/entrepreneurial model has been shown to stimulate innovation in a wide range of technology settings (software, computers, Internet, electronics, et cetera), it wasn't designed to deal with the costs, risks, and slow payout of science-based industries. Although venture capital continues to flow into industries like biotechnology, there has been a significant shift away from funding ventures at the earliest stages. A key concern is that lack of availability of future rounds of financing can shut off the flow of venture capital funding abruptly. In this article, authors Andrew W. Lo and Gary P. Pisano draw on comparisons to projects in the moviemaking industry and propose the project-focused organization (PFO) as an alternative structure for undertaking long-term, high-risk, highly capital-intensive R & D programs in science-based industries such as biotech. PFOs are entities created to conduct a specific R & D project. The authors discuss how they could work in practice, using the example of biopharmaceutical R & D. Researchers innovating in a science-based context must overcome two specific challenges. First, they need to raise sufficient capital to fund a long-term, highly risky, and very expensive project. Second, they must have a governance mechanism for allocating capital (human and financial) and conducting projects. The authors propose that governance centered on the project rather than the company may be a more efficient way to organize innovation in science-based industries. To reduce overhead, they propose contracting out for resources as necessary. As with movie projects, investors could choose projects they want to invest in, with the understanding that they will receive returns only if those projects succeed. Although the authors write that organizing innovation through PFOs has benefits for investors and companies, they say that one size doesn't fit all when it comes to organizing innovation and that many models need to be explored. The article also contains commentaries on Lo and Pisano's ideas by Phillip Sharp of MIT's Koch Institute for Integrative Cancer Research, Noubar Afeyan of Flagship Ventures, Mark E. Davis of the California Institute of Technology, and Josh Lerner of Harvard Business School.
Keywords: Entrepreneurship; Success in business; Entrepreneuriat; Succès dans les affaires; entrepreneurs